Assessment of Enterprise Efficiency Factors Affecting Its ESG Rating - Rutskiy, Vladislav; Marqas, Ridwan Boya; Senapati, Biswaranjan; Muda, Iskandar; Mikhail, Smolik; Shadmanbekova, Kamola A.; Tsarev, Roman (Springer International Publishing Ag, 2024)
The paper is devoted to identifying the efficiency factors of enterprise activity that affect its ESG rating. Companies in many countries are interested in improving their ESG ratings. Thus, business entities demonstrate their commitment to sustainable development principles to their stakeholders, considering environmental and social factors and responsible management of economic resources. ESG management principles today have a significant impact on the activities of companies, consumers, and investors. The authors of this paper have analyzed the methods of compiling ESG ratings by various agencies. Using the example of several largest Russian companies included in national ESG ratings, the authors have identified and tested the relationship between various financial and non-financial factors of enterprise performance and its ESG rating. The results of the econometric modeling showed that the ESG rating of Russian companies is positively associated with capital profitability, stock returns, and the level of carbon dioxide emissions. This may indicate a more mature state of activities of large enterprises that are concerned with ESG compliance due to the scale of their activities and are interested in offsetting their carbon footprint by developing other ESG areas. There is a negative relationship observed between the ESG rating and the company's revenue growth rate. This may indicate that a larger companies demonstrate a relatively lower revenue growth rate, and more dynamic companies are less likely to pay attention to ESG management issues. #CSOC1120
13th Computer Science Online Conference -- APR 25-28, 2024 -- CZECH REPUBLIC
Keywords: enterprise ESG rating; green economy; enterprise efficiency factors